In vitro T2 relaxivities of the Gd-based contrast agents (GBCAs) in human blood at 1.5 and 3 T. (June 2019) - Shen, Yaqi; Goerner, Frank L; Heverhagen, Johannes T; Snyder, Christopher; Hu, Daoyu; Li, Xiaoming; Runge, Val M
Background: The availability of data in the medical literature for the T2 relaxivities of the Gd-based contrast agents (GBCAs) is limited. A comprehensive comparison between the agents available commercially (other than in Europe) is lacking, with no data available that most closely reflect the clinic, which is in human whole blood at body temperature. Purpose: To complement the existing literature by determining T2 relaxivity data for eight GBCAs in vitro. Material and Methods: The relaxivities of eight GBCAs diluted in human whole blood at 1.5 and 3 T were determined at 37 ± 0.5 °C. Gd was in the range of 0–4 mM. Multi-echo sequences with variable echo times were acquired using a phantom containing a dilution series with each agent, and SigmaPlot 12.0 was used to calculate the R2 relaxation rate and finally r2 . Statistical comparisons between agents and field strengths were conducted. Results: The relationship between R2 vs. Gd was observed to be linear at 1.5 and 3 T, with a mild increase in r2 from 1.5 to 3 T for all GBCAs. T2 relaxivity data were compared with prior results. The GBCAs are closely clustered into two groups, with higher r2 noted for the two lipophilic (those with partial hepatobiliary excretion) compounds. Conclusion: The r2 values at 1.5 and 3 T, determined for the eight GBCAs still clinically available (other than in Europe), provide a definitive baseline for future evaluations, including theoretical calculations of signal intensity and their clinical impact on T2-weighted scans.